DELIGNIFIKASI AMPAS TEBU DENGAN LARUTAN NATRIUM HIDROKSIDA SEBELUM PROSES SAKARAIFIKASI SECARA ENZIMATIS MENGGUNAKAN ENZIM SELULASE KASAR DARI ASPERGILLUS NIGER FNU 6018 - Gunam, Ida Bagus Wayan; Wartini, Ni Made; Dewi Anggreni, Anak Agung Made; Suparyana, Pande Made (LIPI Press, 2011)
Cellulose, the most abundant renewable resource, has received much attention as potential energy and carbon source for the production of useful products such as glucose, ethanol and fuels. The possibility of converting cellulose in bagasse enzymatically into glucose, after being loosened its complex structure chemically into primary one by using sodium hydroxide was studied. Bagasse was soaked in 6% sodium hydroxide for 12 hours at room temperature. This treatment resulted in loosening some cellulose bundle structure shown by release of lignin and hemicelluloses up to 32.11 and 42.87%, respectively and high water retention value of 15.90 (w/w). In this condition the delignifi ed bagasse could be saccharifi ed by crude cellulase enzym from Aspergillus niger. Saccharifi cation enzimatically of 2 g delignifi ed bagasse at 50oC pH 4,8 during 120 hours produced reducing sugar of 54.47 mg/100 ml.